Privatisation - a history and survey of changes in organisation structures, cultural and environmental profiles - Gowland, David; Aiken, Max (2003)
This paper provides a brief history of changes after privatisation to organisational structures and cultural profiles of affected entities. It assesses the experience of change in the electricity industry in New Zealand, the Commonwealth Serum Laboratories and the State Electricity Commission of Victoria and then examines results of a survey of senior executives of organisations privatised in Australia between 1990 and 1998. These senior executives had access to knowledge of pre- and post-privatisation conditions and their answers to a series of questions on organisational structure, cultural and environmental issues were analysed. The detailed answers involve limited areas of `no change' but, critically, significant cultural changes relating to private ownership are established. These are summarised for readers' convenience by tables and discussed within the text. - Reproduced.
Keywords: Power industry; Privatization; Organizational change